2007
DOI: 10.1113/expphysiol.2007.038703
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of type 2 diabetes mellitus on cardiac muscle contraction in the Goto‐Kakizaki rat

Abstract: Type 2 diabetes mellitus accounts for more than 90% of all cases of diabetes mellitus, and cardiovascular complications are the major cause of mortality and death in diabetic patients. The chronic effects of type 2 diabetes mellitus on heart function have been investigated in the Goto-Kakizaki (GK) rat. Experiments were performed in GK rats and age-matched Wistar control rats at 18 months of age. The progressive effects of diabetes on glucose metabolism were monitored periodically by application of the glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 38 publications
4
37
0
Order By: Relevance
“…The time course of myocyte shortening and relaxation was reduced in GK-HFD compared with GK-LFD rats. Previous studies, in older rats eating normal rat chow, have demonstrated unaltered amplitude of shortening and reduced time course of relaxation in myocytes from GK rats compared with age-matched control animals (Howarth et al 2007). Interestingly, some previous experiments performed in healthy rats have shown that HFDs resulted in depressed peak myocyte shortening and prolonged time course of shortening and relengthening (Relling et al 2006;Ren et al 2008), and sucrose-enriched diet resulted in prolonged time course of myocyte shortening (Howarth et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time course of myocyte shortening and relaxation was reduced in GK-HFD compared with GK-LFD rats. Previous studies, in older rats eating normal rat chow, have demonstrated unaltered amplitude of shortening and reduced time course of relaxation in myocytes from GK rats compared with age-matched control animals (Howarth et al 2007). Interestingly, some previous experiments performed in healthy rats have shown that HFDs resulted in depressed peak myocyte shortening and prolonged time course of shortening and relengthening (Relling et al 2006;Ren et al 2008), and sucrose-enriched diet resulted in prolonged time course of myocyte shortening (Howarth et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging has demonstrated reduced myocardial blood flow and reduced ejection fraction, mainly as a result of a reduction in left ventricular longitudinal contraction (Iltis et al 2005). In ventricular myocytes, some studies have shown that the amplitude of shortening and corresponding amplitude of the Ca 2+ transient were unaltered (El Omar et al 2004), whilst in others the amplitude of the intracellular Ca 2+ transient was increased in ventricular myocytes from 18-monthold GK rats (Howarth et al 2007). Feeding normal healthy animals a fat-enriched diet may result in impairments of myocyte function, including depressed peak shortening, prolonged time-to-peak (t peak ) shortening and time to relengthening, and reduced intracellular Ca 2+ release and Ca 2+ clearing rate (Howarth et al 2005;Relling et al 2006;Dong et al 2007).…”
mentioning
confidence: 99%
“…In the streptrozotocin treated rats there is a cardiomyopathy, which is characterized by reduced contractility force, relaxation time, and cardiac work [3]. Diabetic cardiomyopathy is a common complication leading to heightened risk of heart failure and death [4].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed on 10 spontaneously hyperglycaemic adult male GK rats and 10 age-matched Wistar control rats at 8 weeks of age. Fasting blood glucose and glucose tolerance measurements were made following a 7 h fast by previously described methods (Howarth et al 2007). …”
Section: Experimental Modelmentioning
confidence: 99%